Discrete Fractional Solutions of an Associated Laguerre Equation - Yilmazer, Resat; Bas, Erdal (Amer Inst Physics, 2018)
In this article, we will give theorems for the discrete fractional solutions of the homogeneous and nonhomogeneous associated Laguerre equation by using discrete fractional nabla operator.
6th International Eurasian Conference on Mathematical Sciences and Applications (IECMSA) -- AUG 15-17, 2017 -- Budapest, HUNGARY